Implementation Of Occupational Health In Improving MSME Productivity In Bandung City - Harun Heri Trismiyanto (Jurnal Ekonomi, 2024)
This study examines the effects of training and the implementation of occupational health in improving MSME productivity in Bandung City during the 2024–2025 period using a quantitative approach. The sample consists of 150 MSMEs selected through stratified random sampling. Data were collected through surveys, in-depth interviews, and field observations. The occupational health training program implemented showed a significant improvement in occupational health practices, with 78% of MSMEs reporting better working conditions. Regression analysis indicates a positive correlation between occupational health implementation and increased productivity, with an average 23% rise in output per working hour. The success of this program is influenced by business owner support, continuous training, and consistent monitoring. This study recommends integrating occupational health programs into MSME development policies at the city and provincial levels. The comprehensive approach of this research provides new insights into measuring the impact of occupational health on MSME productivity while identifying key success factors that have been rarely discussed in the literature.